SOCIAL SUPPORT THROUGH FAMILY COPING MECHANISMS FOR CHILDREN WITH MENTAL RETARDATION IN SPECIAL NEEDS SCHOOL (SLB) BANDA ACEH - Desreza, Nanda; Putra, Yadi; Wedia, Novita (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2023)
Mental retardation is a condition in which mental development is below average since birth or childhood, typically associated with overall lower intellectual development. The global prevalence of mental retardation in children is 14.8%. According to the 2018 Basic Health Research (Riskesdas) data, the prevalence of mental disorders and emotional disabilities in Indonesia was 9.8%, marking a 6% increase compared to 2013. The disability rate among children aged 5-17 in Indonesia is 3.3%, which includes cases of mental retardation. This study aims to explore the relationship between social support and coping mechanisms in families with mentally disabled children attending Special Needs Schools (Sekolah Luar Biasa) in the city of Banda Aceh in 2023. The research methodology is analytical, with a total population of 50 individuals. The sample consists of 50 parents of mentally disabled children selected through purposive sampling. The research was conducted from January 7th to 12th, 2023, and involved both univariate and bivariate analyses. The study's results indicate that out of 50 respondents, the most common type of social support is instrumental support, with 33 individuals (66%), and the majority of coping mechanisms fall into the adaptive category, with 35 individuals (70%). The p-value obtained is 0.004, suggesting a significant correlation between social support and coping mechanisms among parents of mentally disabled children. Hence, parents should keep learning about intellectual disabilities and become better at taking care of children with such challenges.